Responsibilities of Local Governments in Creating a Child-Friendly City in Gorontalo City - Pinoi, Ramli; Marwan, Marwan; Nusa, Apriyanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The government, through Regional Regulation (Perda) of Gorontalo City Number 7 of 2019 concerning the Implementation of Child-Friendly Cities, has promoted the establishment of Child-Friendly Cities (KLA) in Gorontalo City. This study aims to determine the implementation of the Gorontalo City government's responsibilities in realizing child-friendly cities. And what obstacles are faced in implementing the Gorontalo City government's responsibilities in realizing child-friendly cities. Using the Normative-Empirical Legal research method (applied law research), which is a research that uses normative-empirical legal case studies in the form of legal behavior products, with the research results Implementation of the responsibility of the Gorontalo City Regional Government in realizing a Child-Friendly City in terms of policy. The regional government has developed a number of policies that regulate the protection, fulfillment of children's rights to education, health, and participation, as well as empowering institutions related to children such as the Children's Forum and Integrated Posyandu and Implementation of the responsibility of the Gorontalo City Regional Government in realizing a Child-Friendly City in terms of activity programs in fulfilling children's rights. The Gorontalo City Regional Government has implemented various activities aimed at fulfilling children's basic rights, such as education, health, protection, and participation